KEPEMIMPINAN DAN PERILAKU ORGANISASI - Wahab Wahab (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
Leadership is a process of influencing other people to achieve desired goals.Organizational behavior is the relationship between individuals and various things as a form of interaction between individuals and groups in achieving organizational goals and effectiveness. Organizational behavior is very influential progress of an organization. Without a leader, the organizational goals that have been set will not be achieved because each member will only move or try to achieve their personal goals. Organizational behavior (PO) is an applied science, so the science of organizational behavior cannot be separated from the influence of behavioral science so that it contributes to several other behavioral sciences. The goals of leadership are to help create a good social climate, help the group in establishing work procedures, help the group to organize itself, make decisions together with the group and give the group the opportunity to learn from experience.